Differences in trunk angles through different shooting directions in water polo penalty shooting - Jung, C.; Ryu, J.; Park, S.; Lim, H.; Park, S.; Kim, J.; Park, J.; Yoon, S. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to investigate three-dimensionally the shooter`s trunk motion through 4 different shooting directions. Ten Korean national level water polo players who are right-handed were participated in this study (age, 21.60±3.20 years; weight, 86.30±8.86 kg; height, 1.83±0.05 m). To analyze the shooter`s trunk motion among different target, a three-dimensional motion analysis with six video cameras was performed.The analysis events were coking when the trunk was externally rotated maximally and release moment. A one-way ANOVA with repeated measure was performed as main statistical tests and Bonferroni correction was used as a post-hoc test. The results showed that there was statistically significant difference in trunk angle between left and right shooting directions. Especially, the posterior leaning and external rotation angles of trunk in cocking moment were bigger in left shooting direction compared to right one (p<.05). These results suggest that goalkeepers predict shooting direction more precisely by identifying the trunk posture at coking moment.